FAKTOR - FAKTOR YANG MEMPENGARUHI PERILAKU DISFUNGSIONAL AUDIT (Studi Empiris Pada KAP Di Jawa Tengah) - Septiyana Widiyastuti, 12.05.52.0186; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of locus of control, organizational commitment, performance, emotional spiritual question, turnover intention, and audit fee which directly influence acceptance of auditor to dysfunctional behavior. The population in this study were all auditors working in the public accounting firm in Central Java. Sampling was done using purposive sampling method and sample size were 77 respondents. The primary data collection method used was a questionnaire method. Data were analyzed using multiple linier regression model. Result of research indicate that the variables: locus of control, and turnover intention have significant positive effect to acceptance of dysfunctional audit behavior, organizational commitment and emosional spiritual question have significant negativ effect to acceptance of dysfunctional audit behavior, while auditorâs performance do not has a significant negativ effect to acceptance of dysfunctional audit behavior, and audit fee do not has a significant negativ effect to acceptance of dysfunctional audit behavior.Keywords: Locus Of Control, Organization Commitment, Auditor Performance, Emotional Spiritual Question, Turnover Intention, Audit Fee, Dysfunctional Audit Behavior